Cost Estimates and Policy Challenges of Transporting Renewable Energy Derived Ammonia from Gujarat, India to Japan - Takuma Otaki; Rajib Shaw (Hydrogen, 2023)
With growing concern about risks related to energy security around the world, the development of hydrogen cooperation between India and Japan has become very important to ensure the economic security of the two countries and to deepen economic cooperation. This study visualizes the costs and economic issues involved in transporting Ammonia from India to Japan and discusses the policy support needed to establish a hydrogen supply chain between the two countries. If Hydrogen production is conducted in Gujarat and Ammonia production is conducted using Haber–Bosch at a large-scale Ammonia plant, the price of Ammonia at the port of Tokyo can be reduced to 572 USD/mt-NH3 if highly competitive renewable energy is utilized. For evaluating the characteristics of Ammonia produced in India, high contribution to greenhouse gas reduction, low transportation risk along transportation routes, and contribution to the diversification of energy procurement in Japan should be evaluated economically, and the following five initiatives will accelerate the composition of a Hydrogen value chain between India and Japan: (1) increasing the Indian governmental support for subsidies for Hydrogen production, (2) increasing financial support to lower capital costs, (3) ensuring a business environment to lower uncertainty about future costs, (4) promoting efforts to visualize the value of carbon credits such as JCM, and (5) visualizing the value of diversification of energy procurement sources for Japan. A graphical abstract is to follow.